The Role of Attention in Conscious Recollection - De Brigard, Felipe (Frontiers in Psychology, 2012)
Most research on the relationship between attention and consciousness has been limited to perception. However, perceptions are not the only kinds of mental contents of which we can be conscious. An important set of conscious states that has not received proper treatment within this discussion is that of memories. This paper reviews compelling evidence indicating that attention may be necessary, but probably not sufficient, for conscious recollection. However, it is argued that unlike the case of conscious perception, the kind of attention required during recollection is internal, as opposed to external, attention. As such, the surveyed empirical evidence is interpreted as suggesting that internal attention is necessary, but probably not sufficient, for conscious recollection. The paper begins by justifying the need for clear distinctions among different kinds of attention, and then emphasizes the difference between internal and external attention. Next, evidence from behavioral, neuropsychological and neuroimaging studies suggesting that internal attention is required for the successful retrieval of memorial contents is reviewed. In turn, it is argued that internal attention during recollection is what makes us conscious of the contents of retrieved memories; further evidence in support of this claim is also provided. Finally, it is suggested that internal attention is probably not sufficient for conscious recollection. Open questions and possible avenues for future research are also mentioned.